SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/159186-ms
|View full text |Cite
|
Sign up to set email alerts
|

ESP Technology Maturation: Subsea Boosting System With High GOR and Viscous Fluids

Abstract: This paper provides insight into the Caisson ESP Technology Maturation for subsea boosting systems with high GOR and viscous fluids. It will focus on the developmental research on the effects of viscosity and two phase (liquid & gas) fluids on electric submersible pumps (ESPs), which are multistage centrifugal pumps for deep boreholes. The Electrical Submersible Pump (ESP) system is an important artificial lift method commonly used for subsea boosting systems. Multiphase flow and viscous flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…A few scholars conducted a series of theoretical and experimental studies on the submersible pump system. Barrios et al 9 found that the calculated values of the pressure increase produced by the impeller in a submersible pump are similar to the experimental data. The analysis of flow streamlines and its behavior used in CFD was also discussed.…”
Section: Introductionsupporting
confidence: 54%
“…A few scholars conducted a series of theoretical and experimental studies on the submersible pump system. Barrios et al 9 found that the calculated values of the pressure increase produced by the impeller in a submersible pump are similar to the experimental data. The analysis of flow streamlines and its behavior used in CFD was also discussed.…”
Section: Introductionsupporting
confidence: 54%
“…Second, constructing and testing physical prototypes are expensive and time-consuming endeavors, which reduce the profit margins of pump manufacturers. Consequently, several studies have been conducted on CFD to serve as guides for pump design and optimization [5][6][7][8][9][10][11][12][13][14]. In terms of pressure pulsation and radial force, Gao et al [15] studied the static performance and pressure fluctuation of a large centrifugal pump and determined the main frequency of mine monitoring points; their findings agreed well with experimental data.…”
Section: Prefacementioning
confidence: 68%
“…The gaseous phase can also cause severe problems. These include corrosion, gas lock, and a surface kick (Barrios et al 2012;Dwitiya et al 2015;Mali et al 2020).…”
Section: Multiphasementioning
confidence: 99%